2018
DOI: 10.1016/j.bpsc.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hippocampal Volumes and Posttraumatic Stress Disorder Symptoms Over Early Posttrauma Periods

Abstract: Background Smaller hippocampal volume is associated with more severe posttraumatic stress disorder (PTSD) symptoms years after traumatic experiences. Posttraumatic stress symptoms appear early following trauma, but the relationship between hippocampal volume and PTSD symptom severity during early post-trauma periods is not well understood. It is possible that the inverse relationship between hippocampal volume and PTSD symptom severity is already present soon after trauma. To test this possibility we prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Importantly, smaller hippocampal volumes at T1 were also evident for the victims who developed PTSD six months post‐trauma, but not for the victims who did not develop PTSD; this was in the context of identical hippocampal volumes between the victim groups when measured six months post‐trauma. These findings are consistent with small hippocampal volumes being a risk factor to develop PTSD when exposed to a traumatic event . In addition, consistent with previous reports, diurnal cortisol changes at T1 were not associated with the development of PTSD symptoms or hippocampal volumes at T2 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, smaller hippocampal volumes at T1 were also evident for the victims who developed PTSD six months post‐trauma, but not for the victims who did not develop PTSD; this was in the context of identical hippocampal volumes between the victim groups when measured six months post‐trauma. These findings are consistent with small hippocampal volumes being a risk factor to develop PTSD when exposed to a traumatic event . In addition, consistent with previous reports, diurnal cortisol changes at T1 were not associated with the development of PTSD symptoms or hippocampal volumes at T2 .…”
Section: Discussionsupporting
confidence: 92%
“…found that trauma‐exposed veterans had similar hippocampal volumes relative to a healthy comparison group, indicating that reduced hippocampal volume may not be the result of stress and/or trauma exposure . Consistently, a recent prospective study indicates that in the context of no changes in hippocampal volume between 2 weeks and 3 months following a motor vehicle accident, small hippocampal volumes were associated with increased risk for PTSD and re‐experiencing symptoms in this population . Finally, there is to date no clear consensus on the relationship between cortisol dysregulation and hippocampal/amygdala volumes in the development of PTSD: while chronicity of stress exposure, rather than stress exposure itself, may be neurotoxic for stress‐sensitive brain regions , a recent study in veterans reported no associations between salivary cortisol indices and hippocampal/amygdala volumes .…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, volumetric reductions in the hippocampus are commonly reported in studies of PTSD/PTSS in adults (Bonne et al, 2009;Logue et al, 2018;Woon, Sood, & Hedges, 2010), which may reflect a negative neurobiological response to stress. However, studies in youth are inconsistent regarding the effects of early stress and/or PTSS in children and adolescents (Shucard et al, 2012;Xie et al, 2018). In light of these discrepancies, several authors have suggested that volumetric reductions observed in adults may unfold over time and are thus not evident in pediatric samples (Malhi et al, 2019;Teicher et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A number of scholars have suggested hippocampal volume is a biomarker of risk for PTSD development (i.e., vulnerability factor; Gilbertson et al, 2002 ; Gurvits et al, 2006 ; Kremen et al, 2012 ; Wang et al, 2010 ; Xie et al, 2018 ) and/or asserted that changes in volume track with PTSD symptoms (i.e., are caused by the resulting psychological sequela; Apfel et al, 2011 ; Gurvits et al, 1996 ; Woon and Hedges, 2008 ). Although more sparse, additional work has demonstrated null findings, suggesting smaller hippocampus volume is neither a risk factor nor a consequence of PTSD (e.g., Bonne et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the aforementioned research, we hypothesized that smaller global hippocampal volume (T1) would prospectively relate to T3 PTSD symptoms ( Gilbertson et al, 2002 ; Gurvits et al, 2006 ; Kremen et al, 2012 ; Wang et al, 2010 ; Xie et al, 2018 ). We also hypothesized smaller global hippocampal volume ( Apfel et al, 2011 ; Gurvits et al, 1996 ; Woon and Hedges, 2008 ), as well as smaller dentate gyrus/CA4 and CA1 (measured at T3) would be significantly related to T3 PTSD symptoms ( Hayes et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%